Efficient Synthesis of Functionalized Pyrido[2,3-c]coumarin Derivatives by a One-Pot Three-Component Reaction - Chen, Zhiwei; Hu, Lele; Peng, Fei (Synlett, 2016)
A methanesulfonic acid promoted three-component reaction has been developed for the synthesis of functionalized pyrido[2,3-c]coumarin derivatives from ketones, aromatic aldehydes, and 3-aminocoumarin. In this simple and efficient protocol, products were obtained in moderate to good yields (28 examples). The reaction proceeds by an asynchronous [4+2] cycloaddition (inverse-electron-demand Diels–Alder reaction).
Keywords: multicomponent reactions; pyridocoumarins; ketones; aldehydes; cycloaddition reactions